2009
DOI: 10.1007/s10439-009-9797-8
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Crack Resistance of Interstitial, Osteonal and Trabecular Bone Tissue

Abstract: The purpose of this work was to investigate differences which may exist in the crack resistance of the microstructural bone tissues, i.e., osteonal, interstitial and trabecular bone. Indentations, using varying loads were used to initiate cracks of the same size scale as those which exist habitually in bone. The crack lengths and corresponding toughness values are presented for each of the tissues. Specimens were prepared using standard nanoindentation preparation techniques. Young's modulus and hardness were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Bone is a connective tissue mainly composed of mineral and type I collagen, which determines the hardness and strength of bones [ 16 , 17 ]. Micro-indentation and ultrasound techniques have been used to determine the hardness and strength of bones [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bone is a connective tissue mainly composed of mineral and type I collagen, which determines the hardness and strength of bones [ 16 , 17 ]. Micro-indentation and ultrasound techniques have been used to determine the hardness and strength of bones [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…cement lines) help to attenuate energy of microdamage, thereby restricting propagation (Gibson et al 2006). Indeed, Mullins et al (2006) have demonstrated that the severity of microdamage, as measured by crack length, is much greater in areas of interstitial bone and much less severe in areas of osteonal bone. Therefore, higher remodeling density found in the anterolateral femoral cortex in this study might be evidence of an adaptive toughening mechanism in response to habitual tension/shear loading in this region to reduce the severity of microdamage experienced.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of bone quantity on the mechanical behaviour and structural integrity of bone was established previously [5,6], however, more in-depth investigations are still required of the contributory effects of microstructure, material properties, and microcrack propagation [3,7]. These can be characterized as bone quality measures; an improved understanding of bone quality, particularly, resistance to crack initiation and propagation can help in accessing bone fracture risk [8]. It is well known that damage occurs in both trabecular and cortical bone due to daily activity loading regime [9].…”
Section: Introductionmentioning
confidence: 98%
“…Evolution of damage in our models is defined based on the energy required for failure (fracture energy) after the initiation of damage. The stress intensity factor for the homogenised material is based on data from Nalla et al [30], and those for osteons and interstitial bone were taken by guidance from [8]. A ratio, ⁄ = 2 where and are interstitial bone and cement line stress intensity factors, were utilized to obtain the cement line stress intensity factor based on [31].…”
Section: Xfem-based Cohesive Behaviour and Fracture Propertiesmentioning
confidence: 99%